L’Académie d’Égypte à Rome, miroir des politiques culturelles étatiques pour les arts visuels (2001-2011) - Catherine Cornet (Revue des Mondes Musulmans et de la Méditerranée)
The Academy of Egypt in Rome is a unique institution in the panorama of state cultural institutions : it is the most important Egyptian cultural centre in the world and the main showcase of Egyptian art in Europe. Through an in-depth study of both the Academy’ cultural actors and the artists’ works and narratives that are associated to the Academy though exhibitions or grants received between 2001 and 2011, the study allows to grasp the official state narrative on the arts during this decade. The Academy of Egypt still represents an important reference point for the local art scene, but it also illustrates the pulling off of the Mubarak State in the last decade of his presidency. The State does not produce its own narrative anymore except for the loose concepts of ‘modernity’ or ill-defined ‘authenticity’. If the Academy interestingly keeps alive several historical cultural trends, from the Nasserist tradition of mass education or the centrality of Ancient Egypt in a national perspective, it also testifies of an official cultural scene engaged in the struggle against the rise of Political Islam during this decade that has heavily structured the cultural field.